Multibeam bathymetry processed data (Kongsberg EM 122 working area dataset, Generic sensor format) of RV MARIA S. MERIAN during cruise MSM112/2, Atlantic Ocean - Gavin D extquotesingleMello; Gustavo Binda Souza; Frank Nitsche; Harald Sternberg (PANGAEA, 2023)
The multibeam echo sounder (MBES) data was collected from the 24.11.2022 (02:52 UTC) to the 03.12.2022 (22:52 UTC) with the Kongsberg EM122 on RV Maria S. Merian during the transit from Cartagena (Colombia) to Las Palmas (Canary Islands, Spain) in the Atlantic Ocean. The deep-water MBES EM122 operates with an acoustic frequency of 12 kHz and a beam opening angle of 2° x 2°. The system was used in the dual-swath mode with up to 864 beams per ping. During the acquisition the echo sounder was monitored as well as settings and filter adjusted according to the environment. The swath opening angle was set between 65° and 70°. As the data was collected during transit, no specific survey was performed. Sound velocity profiles (SVP) were measured on the 23.11., 25.11., 29.11., and 30.11.22 with a CTD and applied in the MBES acquisition software SIS to ensure high quality measurement. The SVP data is not part of this submission but can be extracted from the *.all files. The data was post-processed using the software QPS Qimera. No further navigation or tide correction was applied. The SVP profiles were re-applied to the data by using the nearest in time. Erroneous depth measurements were deleted manually by using the swath and slice editor. The vertical datum is mean sea level (MSL). The cleaned data was exported in gsf format.